Rational fusion design inspired by cell-penetrating peptide: SS31/S-14 G Humanin hybrid peptide with amplified multimodal efficacy and bio-permeability for the treatment of Alzheimer's disease - Kang Qian; Peng Yang; Yixian Li; Ran Meng; Yunlong Cheng; Lingling Zhou; Jing Wu; Shuting Xu; Xiaoyan Bao; Qian Guo; Pengzhen Wang; Minjun Xu; et al. (Elsevier, 2024)
Alzheimer's disease is a neurodegenerative disease induced by multiple interconnected mechanisms. Peptide drug candidates with multi-modal efficacy generated from fusion strategy are suitable for addressing multi-facet pathology. However, clinical translation of peptide drugs is greatly hampered by their low permeability into brain. Herein, a hybrid peptide HNSS is generated by merging two therapeutic peptides (SS31 and S-14 G Humanin (HNG)), using a different approach from the classical shuttle-therapeutic peptide conjugate design. HNSS demonstrated increased bio-permeability, with a 2-fold improvement in brain distribution over HNG, thanks to its structure mimicking the design of signal peptide-derived cell-penetrating peptides. HNSS efficiently alleviated mitochondrial dysfunction through the combined effects of mitochondrial targeting, ROS scavenging and p-STAT3 activation. Meanwhile, HNSS with increased Aβ affinity greatly inhibited Aβ oligomerization/fibrillation, and interrupted Aβ interaction with neuron/microglia by reducing neuronal mitochondrial Aβ deposition and promoting microglial phagocytosis of Aβ. In 3× Tg-AD transgenic mice, HNSS treatment efficiently inhibited brain neuron loss and improved the cognitive performance. This work validates the rational fusion design-based strategy for bio-permeability improvement and efficacy amplification, providing a paradigm for developing therapeutic peptide candidates against neurodegenerative disease.